Integration Of Islamic Values Relating To The Doctor’s Profession Curriculum - Dwi Hikmah; Sri Julyani; M. Khidri Alwi (Sean Institute, 2023)
Science integration is a process to perfect dichotomous knowledge so as to produce a complete scientific concept. Curriculum objectives contain competency standards to be achieved from ongoing learning or in simpler language, curriculum objectives, namely what student output will result from learning. A medical education curriculum that integrates Islamic content is a necessity for Muslim doctors. The importance of integrating Islam into the medical education curriculum is to provide provisions for Muslim doctors when facing ethical issues related to the Islamic religion. In order not to stop at just philosophical discourse, the implementation of Islamic integration in medical science must be reflected in curriculum development and learning.